Bona fide elements relating to directors' duties / Nur Safrisha Mohd Safawat Hossain - Mohd Safawat Hossain, Nur Safrisha (2005)
Since late 1990's, many Commonwealth countries such as Malaysia, Australia and New Zealand has been actively conducting their Law Reforms especially in the area of Company Law1. A common issue which most of these jurisdictions are heavily harping on is the area of directors5 duties. This area has been evolving through time and still developing till to date. It seems to be an area of concern for many parties such as the regulators, corporations and professionals due to the fact that the law has come up with many tools which conferred such wide powers to the directors resulting them abusing those powers in mismanagement and breaching their duties. A very strong point was highlighted by Farwell LJ in Gramaphone & Typewriter Ltd v Stanley2 on the strength of the powers of directors conferred by the articles of the company and how even the body of shareholders as the owner of the company are only able to challenge those powers through two drastic actions that is, either by altering the articles or by refusing to reelect the director in the next general meeting.